Therapeutic Approaches to Tackle the Challenge of Depression That Is Resistant to Treatment–A Narrative Review - Md. Rajdoula Rafe; Abdul Waris; Pranoy Saha (Health Science Reports)
ABSTRACT Background and Aims The lack of therapeutic response characterizes treatment‐resistant depression despite undergoing at least two adequate monotherapy trials with medications from distinct pharmacologic classes. The inability to attain remission in patients diagnosed with major depressive disorder (MDD) is a significant issue of concern within public health. Therefore, the management of treatment‐resistant depression (TRD) poses significant obstacles for both patients and healthcare professionals. Our goal was to investigate the published literature concerning different options for treatment for TRD, including those that do not involve the use of medications. Methods We thoroughly searched the literature in the Google Scholar, PubMed, and ScienceDirect databases to find publications relevant to our narrative review and extracted data from appropriate data. For this review, literary works written solely in English were chosen. Results Ongoing research is being conducted to explore the treatment options for TRD, including pharmacological and nonpharmacological interventions. Pharmacological interventions include a wide range of therapeutic approaches, including but not limited to investigating innovative medications and strategies such as augmentation, switching, and combination therapies involving established and emerging drugs. Nonpharmacological interventions, including brain stimulation such as theta burst stimulation, deep brain stimulation, electroconvulsive therapy, repetitive transcranial magnetic stimulation, intermittent transcranial magnetic stimulation, and magnetic seizure therapy, as well as psychotherapeutic approaches, are being explored for the management of TRD in both present and future contexts. Conclusion Researchers are dedicating significant resources to the aforementioned therapeutic interventions to advance the development of novel and efficacious treatment options for TRD and enhance our comprehension of the underlying disease. This review focused on looking at recent research concerning therapeutic interventions for TRD.